Análisis del silencio organizacional en la Universidad Francisco de Paula Santander Ocaña, Colombia - Liceth Arévalo-Pérez; Elvis Ríos-Pacheco; Héverd Augusto Páez-Quintana (Mundo Fesc)
This article presents the results of a research project entitled Organizational Silence at Francisco de Paula Santander Ocaña University, Colombia. Its main objective was to analyze the causes and impacts of organizational silence on the institution's employees. The research was conducted using a mixed approach and a DITRAC (concurrent triangulation) design with an exploratory and descriptive scope. Surveys and in-depth interviews were used to collect data, allowing triangulation of information and epistemological comparisons on the topic studied. Among the most relevant results of the research are the types of fear perceived by employees at the institution. Furthermore, the possible reasons why employees experience organizational silence were identified, including: the need to avoid retaliation and conflict with other colleagues, since it is important for them to protect the work environment; the lack of freedom to speak with managers and faculty who are hired for an indefinite period of time; meaning that the types of contracts influence organizational silence; and finally that there is a high degree of sense of belonging to the institution.